Studi Manajemen Penyelenggaraan Pameran Seni Rupa Di Bentara Budaya Yogyakarta - Indratmo, Effy; Handayani, Tri Lestyo (Institut Seni Indoensia Surakarta, 2014)
This study discusses about: Bentara Budaya Yogyakarta, management of art exhibitions and curatorial system organizing art exhibitions in Bentara Budaya Yogyakarta. This type of research is descriptive and qualitative object under study is the process of organizing an art exhibition in 2012, and observing and recording systems curatorial art exhibitions in Bentara Budaya Yogyakarta. Data collection techniques such as literature study, observation, interviews, and documentation. The validity technique used is the triangulation of data by leveraging data sources and methods review informant. Data analysis using flow models of analysis (flow models). To explain the process of the management of art exhibitions and curatorial system organizing art exhibitions using the guidebook written by Mikke Susanto. The results showed that: the process of organizing curatorial art exhibitions in Bentara Budaya Yogyakarta in its implementation is divided into two types, namely the initiative of artists and gallery managers initiative. Observing the results of the exhibition of art based on the typology and periodization of time organizing art exhibitions, visible differences between the initiative of artists and galleries initiatives in terms of time organizing exhibitions and art galleries pemakiaan procedures.Keywords: arts management, curatorial, Bentara Budaya Yogyakarta